Kegilaan dalam Novel Racun Puan Karrya Ni Nyoman Ayu Suciatrini: Tinjuauan Psikologi Sastra - Khairani, Nabila (Jurnal Ceteris Paribus, 2025)
This research delves into the theme of madness in the novel "Racun Puan" by Ni Nyoman Ayu Suciatrini. The story is set in Bali Province, an area with a high incidence of mental illness. In "Racun Puan," multiple characters, a family comprising a father, mother, and child, grapple with madness. The study aims to explore the psychological challenges faced by the characters and the author's perspective on these issues. To conduct the research, a Literary Psychology review was employed, drawing from Jacques Lacan's Psychoanalysis theory, which explores the formation of the self through the real, imaginary, and symbolic orders. The research applies Lacanian Psychoanalysis to analyze the characters' psychological journeys, beginning with their traumatic experiences (real order), followed by their development in the imaginary order or mirror stage during childhood, and culminating in the symbolic order as they strive to fulfill unmet desires from the real order. Additionally, the author's viewpoint on the characters' psychological struggles is presented as a critique of the patriarchal culture and social caste system in Balinese society, indicating that these systems are no longer relevant in contemporary society and can contribute to mental health issues. The study's findings highlight the psychological impact of Balinese society's patriarchal culture and social structure, which manifest as mental disorders, particularly madness.